Emerging carbon capture technologies : towards a sustainable future - Khalid, Mohammad; Dharaskar, Swapnil A.; Sillanpää, Mika E. T.; Siddiqui, Humaira (Elsevier, 2022)
Carbon dioxide (CO2) capture and conversion to value added products, such as chemicals, polymers, and carbon-based fuels represents a promising approach to transform a potential threat to the environment into a value-added product for long term sustainability. Emerging Carbon Capture Technologies: Towards a Sustainable Future provides a multidisciplinary view of the research that is being carried out in this field, covering materials and processes for CO2 capture and utilization and including a broad discussion of the impact of novel technologies in carbon capture on the energy landscape, society and climate. Of interest to students, researchers and professionals in industries related to greenhouse gas mitigation, post-combustion CO2 capture processes, coal-fired power plants, environmental sustainability, green solvents, green technologies, and the utilization of clean energy for environmental protection, this book covers both the experimental and theoretical aspects of novel materials and process development providing a holistic approach toward a sustainable energy future.